2010
DOI: 10.1080/08870440802311314
|View full text |Cite
|
Sign up to set email alerts
|

On the importance of a positive view on ageing for physical exercise among middle-aged and older adults: Cross-sectional and longitudinal findings

Abstract: Physical activity is one of the most important health behaviours associated with the prevention and management of chronic diseases in older adults, but this potential is often insufficiently used. The present study examined for the first time whether a positive view on ageing (PVA) may contribute to a higher level of physical activity. Analyses were based on the German Ageing Survey, a longitudinal population-based survey (N = 4034) on middle-aged and older adults (40-85 years) conducted in the years 1996 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
142
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(158 citation statements)
references
References 50 publications
11
142
5
Order By: Relevance
“…This allowed the researcher to ask follow-up questions, to probe regarding topics 15 which arose, and to gain participant reflections on their previous answers and any 16 changes that may have occurred (Day, 2013). In accordance with Smith (2013), 17 multiple interviews may allow for a more credible and in depth understanding than 18 singular interactions, enhancing the development of trust and rapport between 19 researcher and participant.…”
Section: Data Collection and Analysis 18mentioning
confidence: 99%
See 2 more Smart Citations
“…This allowed the researcher to ask follow-up questions, to probe regarding topics 15 which arose, and to gain participant reflections on their previous answers and any 16 changes that may have occurred (Day, 2013). In accordance with Smith (2013), 17 multiple interviews may allow for a more credible and in depth understanding than 18 singular interactions, enhancing the development of trust and rapport between 19 researcher and participant.…”
Section: Data Collection and Analysis 18mentioning
confidence: 99%
“…For all three 14 participants, age provided the basis for comparisons, further, the exercise group even 15 served to affirm the relationship between age and deterioration. 16 To facilitate the assimilation of the exercise experience into their existing 17 narratives, participants' focus remained in the here and now when discussing their 18 exercise participation. All three participants reported the benefits associated with 19 exercise, but none discussed the future impact that these benefits would have.…”
Section: Physical Activity and Decelerated Decline 21mentioning
confidence: 99%
See 1 more Smart Citation
“…GPs views on aging are relevant since they might unknowingly maintain certain negative aging stereotypes by promoting negative images of aging in their work. A positive view of aging means that they see the potential for development and experiencing positive emotions in old age, while negative images of aging mean associating old age with illness and dependency (Levy, 2003;Wurm, Tomasik, & Tesch-Römer, 2010). Previous studies showed that health professionals had more negative images of aging (Walter et al, 2010;Craciun & Flick, 2015;Craciun, 2016).…”
Section: Health Professionals and Aging Representationsmentioning
confidence: 99%
“…Engstler, 2006;Scherger et al, 2012), age-related cognitions, activities and health (e.g. Wurm et al, 2007;Böhm et al, 2009;Wurm et al, 2010;Schöllgen et al, 2010;Schöllgen et al, 2012;Schüz et al, 2011), subjective well-being and loneliness (e.g. Westerhof et al, 2006;Wurm et al, 2008;Merz et al, 2010;Wiest et al, 2011;Tesch-Römer et al, 2012), family relations, grandparenthood and social networks (e.g.…”
Section: Main Research Areas So Farmentioning
confidence: 99%